Synthesis, crystal structure and absolute configuration of (3aS,4R,5S,7aR)-7-(but-3-en-1-yn-1-yl)-2,2-dimethyl-3a,4,5,7a-tetrahydro-2H-1,3-benzodioxole-4,5-diol - Alejandro Peixoto de Abreu Lima; Enrique Pandolfi; Valeria Schapiro; Leopoldo Suescun (Acta Crystallographica Section E: Crystallographic Communications)
The absolute configuration of the title compound, C13H16O4, determined as 1S,2R,3S,4R based on the synthetic pathway, was confirmed by single-crystal X-ray diffraction. The molecule is a relevant intermediary for the synthesis of speciosins, epoxyquinoides or their analogues. The molecule contains fused five- and six-membered rings with two free hydroxyl groups and two protected as an isopropylidenedioxo ring. The packing is directed by hydrogen bonds that define double planes of molecules laying along the ab plane and van der Waals interactions between aliphatic chains that point outwards of the planes.